Rekonstruksi Mekanisme Seleksi Hakim Konstitusi di Indonesia - Pangestu, Indah Sri; Yuliani, Dwi; Siburian, Hertaty Dorothy Dewi (UI Scholars Hub, 2025)
The mechanism for selection and election of constitutional judges in Indonesia currently still shows a diversity of procedures in each proposing institution, namely the Supreme Court, DPR and President. The process implemented does not fully reflect the principles of transparency, participation, objectivity and accountability as mandated in the Law on the Constitutional Court. Therefore, it is necessary to standardize the procedures for selection and selection of constitutional judges to ensure a more professional system and integrity. One of the solutions offered is the establishment of an independent institution responsible for the selection and recruitment of constitutional judges with a system that is more open and involves community participation. In this case, the Judicial Commission has the capacity as an institution that can carry out the selection of constitutional judges in a more transparent and accountable manner. Apart from that, as a comparison, this research also analyzes the selection mechanism for constitutional judges in Thailand, which shows that the selection system in that country involves more various stakeholders, so it is considered more inclusive and credible. Thus, the reconstruction of the constitutional judge selection mechanism in Indonesia needs to consider a more standardized and participatory model to produce judges who are professional, have integrity, and are able to maintain the independence of the constitutional justice institution. Keywords: Selection of Constitutional Judges, Judicial Commission, Indonesia-Thailand Comparison.